2016
DOI: 10.3390/metabo6040031
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics and Cheminformatics Analysis of Antifungal Function of Plant Metabolites

Abstract: Fusarium head blight (FHB), primarily caused by Fusarium graminearum, is a devastating disease of wheat. Partial resistance to FHB of several wheat cultivars includes specific metabolic responses to inoculation. Previously published studies have determined major metabolic changes induced by pathogens in resistant and susceptible plants. Functionality of the majority of these metabolites in resistance remains unknown. In this work we have made a compilation of all metabolites determined as selectively accumulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 56 publications
1
14
0
1
Order By: Relevance
“…The monophenolic compound ferulic acid, the most abundant polyphenolic acid compound found in wheat grain, has been shown to function as an efficient inhibitor of type B trichothecene biosynthesis and Tri gene expression in Fg in liquid cultures (Boutigny et al ., , ; Ponts et al ., ). Ferulic acid also shows growth inhibitory activity against Fg in vitro (Cuperlovic‐Culf et al ., ). In addition biphenolic flavonoid compounds are also known to inhibit production of T‐2 toxin in F. sporotrichioides (Desjardins et al ., ).…”
Section: Targets In the Tri Gene Clusters Of Don And Nivalenol‐producmentioning
confidence: 97%
See 3 more Smart Citations
“…The monophenolic compound ferulic acid, the most abundant polyphenolic acid compound found in wheat grain, has been shown to function as an efficient inhibitor of type B trichothecene biosynthesis and Tri gene expression in Fg in liquid cultures (Boutigny et al ., , ; Ponts et al ., ). Ferulic acid also shows growth inhibitory activity against Fg in vitro (Cuperlovic‐Culf et al ., ). In addition biphenolic flavonoid compounds are also known to inhibit production of T‐2 toxin in F. sporotrichioides (Desjardins et al ., ).…”
Section: Targets In the Tri Gene Clusters Of Don And Nivalenol‐producmentioning
confidence: 97%
“…In addition biphenolic flavonoid compounds are also known to inhibit production of T‐2 toxin in F. sporotrichioides (Desjardins et al ., ). Indeed, it has recently been shown that the flavonoid compound naringenin inhibits Fg growth in vitro (Cuperlovic‐Culf et al ., ). Further to this, oxidative stress created in liquid cultures of Fg by addition of oxidizing agents such as H 2 O 2 has been shown to cause strong induction of expression of several Tri genes and increased production of TCTB (Ponts et al ., , ).…”
Section: Targets In the Tri Gene Clusters Of Don And Nivalenol‐producmentioning
confidence: 97%
See 2 more Smart Citations
“…In the analysed oat accessions, oxycinnamic, oxybenzoic, pipecolic and 5-hydroxypipecolic acids have been identified. Since the latter are known for their anti-Fusarium activity (Cuperlovic-Culf et al, 2016), it becomes possible to use collections for selecting accessions with the highest concentrations of these compounds as sources of potential resistance to Fusarium.…”
Section: Role Of Individual Metabolites In Building Up Resistance To mentioning
confidence: 99%